Digital follow‐up by means of dermatoscopy and reflectance confocal microscopy of actinic keratosis treated with Imiquimod 3.75% cream. (22nd January 2020) - Benati, E.; Longhitano, S.; Pampena, R.; Mirra, M.; Raucci, M.; Pellacani, G.; Longo, C.
Abstract: Background: Imiquimod 3.75% cream (Zyclara ® Meda, Stockholm, Sweden) is a new field‐directed therapy for actinic keratosis (AK). Objectives: The aim is to evaluate efficacy and the morphologic dynamic changes induced by this treatment by means of dermatoscopy and reflectance confocal microscopy (RCM) of imiquimod 3.75% cream for the treatment of AKs of the face or scalp and to evaluate. Methods: Thirty‐two patients were treated with Imiquimod 3.75% cream. Demographic parameters, AK‐FAS and AKASI scores and side‐effects were collected. RCM and dermatoscopy on one target AKs were performed at each visit. We collected images at baseline (T0), after 1 week from the end of the first 2‐week cycle (T1), after 1 week from the end of the entire treatment (T2) and 2 months after the end of treatment (T3). Results: One target representative AK in the selected area of treatment of each patient was analysed. All dermoscopic and confocal parameters were reduced 2 months after the end of the therapy (T3) with a substantial reduction of AKASI and AK‐FAS scores, and 17 cases (54.8%) were completely solved. Confocal microscopic analysis showed a reduction of keratinocytes disarray in 77.4% of cases; none showed crusts and parakeratosis. Inflammation was considerably decreased and was observed only in 12.9% of patients at the last visit. This improvement was not assessed on dermatoscopy because of inflammation and background erythema, which adversely influenced the assessments. LSRs were observed in almost all the patients during treatment being more severe after the first cycle of treatment (T1). Conclusions: Imiquimod 3.75% cream is effective in treating clinical and subclinical AKs with an easy management of side‐effects. Dermatoscopy and mostly RCM allow non‐invasive monitoring of treatment response in vivo .